Research classification and the social sciences and humanities in Australia: (Mis)Matching organisational unit contribution and the impact of collaboration - Haddow, Gaby (Oxford Journals, 2015)
The capacity to recognize the contribution of individual researchers and their organizational unit is likely to be at odds with the purpose of a national research assessment, due to the broader approach to identifying research strengths and its classification at disciplinary levels. The Australian research assessment exercise, Excellence in Research for Australia (ERA), is devised to determine research quality in this wider context. To explore the impact of research classification on the visibility of research contribution, this study analysed articles published by authors affiliated with two social sciences and humanities (SSH) fields—‘education’ and ‘language, communication and culture’. Article classification was examined for agreement with the authors’ affiliated organizational unit’s field. The influence of national and international co-authorship on article classification was also examined. Articles were distributed across different classification categories and a substantial proportion did not match with the authors’ organizational unit’s field. National and international co-authorship by education-affiliated authors was found to be significantly associated with publishing outside their organizational unit’s field. As the first investigation to focus on how research is distributed by the ERA’s classification scheme when applied to journal articles by SSH authors, the study provides empirical evidence of the challenges involved in recognizing the contribution of organizational units. This work builds on the existing literature relating to classification and research evaluation and has the potential to inform research managers of the complexities in setting strategic research priorities based on ERA outcomes.